2006
DOI: 10.1093/nar/gkj452
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the S.cerevisiae Sgs1 protein facilitates recombinational repair of telomeres during senescence

Abstract: RecQ DNA helicases, including yeast Sgs1p and the human Werner and Bloom syndrome proteins, participate in telomere biology, but the underlying mechanisms are not fully understood. Here, we explore the protein sequences and genetic interactors of Sgs1p that function to slow the senescence of telomerase (tlc1) mutants. We find that the S-phase checkpoint function of Sgs1p is dispensable for preventing rapid senescence, but that Sgs1p sequences required for homologous recombination, including the helicase domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 98 publications
8
69
0
Order By: Relevance
“…Consistent with this idea, studies in human cells have shown that the absence of the WRN DNA helicase, which like its yeast homologue Sgs1p, is particularly adept at unwinding G4-DNA [39,40,42,87], results in loss of the telomere strand that is replicated by lagging strand synthesis [36]. Telomere defects related to replication in sgs1 mutants might have a similar basis [88,89]. Further, the unwinding of telomere quadruplexes during Stylonichia telomere replication [4,5], and the CGG repeat-induced pausing of DNA polymerases in vitro [90,91], are consistent with G4-DNA providing an impediment to replication.…”
Section: G-quadruplexes and Dna Replicationmentioning
confidence: 88%
“…Consistent with this idea, studies in human cells have shown that the absence of the WRN DNA helicase, which like its yeast homologue Sgs1p, is particularly adept at unwinding G4-DNA [39,40,42,87], results in loss of the telomere strand that is replicated by lagging strand synthesis [36]. Telomere defects related to replication in sgs1 mutants might have a similar basis [88,89]. Further, the unwinding of telomere quadruplexes during Stylonichia telomere replication [4,5], and the CGG repeat-induced pausing of DNA polymerases in vitro [90,91], are consistent with G4-DNA providing an impediment to replication.…”
Section: G-quadruplexes and Dna Replicationmentioning
confidence: 88%
“…(C) Precise NHEJ and imprecise NHEJ were performed and analyzed as described in the Materials and Methods on GA-8860 (wild type) and GA-8471 (nup84Δ). yeast mutants that lack functional telomerase (Azam et al 2006). Also, in yeast, eroded telomeres relocate to nuclear pores (V Geli, pers.…”
Section: Discussionmentioning
confidence: 99%
“…Although Scrrm3⌬ cells do not exhibit changes in GCR or mitochondrial genome stability, these cells do exhibit genetic instability, presumably due to replication fork pausing at specific chromosomal loci, such as the ribosomal DNA locus (31,32,45,59,68,69). ScRRM3 and ScPIF1 exhibit genetic interactions (including synthetic lethality) with many gene products required in DNA replication and S-phase checkpoint arrest (1,2,17,50,58,59,69,71). Thus, additional inactivation of other DNA helicases involved in DNA replication or repair or proteins essential for the S-phase checkpoint may yet reveal an interesting phenotype in mPif Ϫ/Ϫ animals.…”
Section: Discussionmentioning
confidence: 99%